Low viscosity taic for photocurable materials and process for its preparation
Patent Information
- Application Number
- CN202610778306.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-13
AI Technical Summary
一方面,现有工艺采用均相催化或酸碱中和体系,导致反应后催化剂难回收,且产生大量成分复杂的含盐、含有机物废水,后处理繁琐,环保压力大
[0020](1)本发明以异氰尿酸、烯丙基甲基碳酸酯为原料,选用负载型固体碱进行催化合成,反应过程中配合减压精馏与惰性气体吹扫,原位连续脱除副产物。相较于现有工艺,本发明可规避氯离子、硫离子、金属盐等离子型杂质引入,所得产物碱值、色度均处于较低水平,既能消除杂质对光固化体系自由基聚合的抑制作用,也可保障产品具备良好的储存稳定性。
Smart Images

Figure CN122897808A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of photocurable materials and fine chemical technology, and in particular to a low-viscosity TAIC for photocurable materials and its preparation process. Background Technology
[0002] Triallyl isocyanurate (TAIC) is a highly efficient crosslinking agent containing three allyl functional groups. It can be used to improve the crosslinking density, heat resistance, and mechanical properties of polymer materials, and has important applications in fields such as photocurable coatings, inks, and 3D printing resins. With the rapid development of photocuring technology, downstream applications have placed stringent requirements on the physical properties of crosslinking agents, especially initial viscosity, color, storage stability, and impurity content.
[0003] Currently, the mainstream industrial technologies for preparing triallyl isocyanurates mainly include the allyl chloride method, the allyl alcohol method, and the triallyl isocyanurate isomerization rearrangement method. On the one hand, existing processes use homogeneous catalysis or acid-base neutralization systems, making catalyst recovery difficult after the reaction and generating large amounts of complex wastewater containing salts and organic matter, resulting in cumbersome post-treatment and significant environmental pressure. On the other hand, conventional processes prioritize chemical yield, lacking refined control and deep purification of the final product's physical properties. The resulting TAIC products typically have high viscosity and contain trace amounts of metal ions, oligomers, and colored impurities, leading to poor storage stability. When used in photocuring systems, they often require heating and melting or the addition of diluents, which not only increases process complexity but also adversely affects the final properties of the cured material, such as volume shrinkage and weather resistance.
[0004] Therefore, there is an urgent need for a low-viscosity TAIC for photocurable materials and its preparation process, so as to obtain products with low viscosity, low color and high purity, and ensure good compatibility between the product and the photocurable formulation system, which can improve the high temperature resistance and yellowing aging resistance of photocurable molded products. Summary of the Invention
[0005] This invention overcomes the shortcomings of the prior art and provides a low-viscosity TAIC for photocurable materials and its preparation process.
[0006] To achieve the above objectives, the technical solution adopted by this invention is: a preparation process for low-viscosity TAIC for photocurable materials, comprising the following steps:
[0007] S1. Isocyanuric acid, allyl methyl carbonate, and a polar aprotic solvent are placed in a reaction vessel, stirred, and nitrogen is introduced to replace the air. A supported solid base catalyst is added. The reaction is stirred at 100-120℃ and 1.0×10⁴-3×10⁴ Pa for 6-8 hours. During the reaction, methanol is removed by distillation and carbon dioxide is removed by purging with inert gas to obtain the reaction solution.
[0008] S2. Cool the reaction solution to 30-45℃, filter to remove the supported solid base catalyst, and collect the filtrate; distill the filtrate under reduced pressure at 80-120℃ and 100-1000Pa using a thin-film evaporator to obtain crude TAIC.
[0009] S3. The crude TAIC is fed into a first-stage short-path molecular distillation apparatus, and crudely separated and the middle distillate is collected under conditions of 120-140℃ and 0.05-0.10Pa. The middle distillate is then fed into a second-stage short-path molecular distillation apparatus, and refined and the middle distillate is collected under conditions of 100-120℃ and 0.01-0.05Pa to obtain the low-viscosity TAIC.
[0010] In a preferred embodiment of the present invention, in step S1, the molar ratio of isocyanuric acid to allyl methyl carbonate is 1:3.0-5.0.
[0011] In a preferred embodiment of the present invention, in step S1, the polar aprotic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, or N-methylpyrrolidone.
[0012] In a preferred embodiment of the present invention, in step S1, the mass ratio of the polar aprotic solvent to the isocyanuric acid is 4-8:1.
[0013] In a preferred embodiment of the present invention, in step S2, the supported solid base catalyst is selected from at least one of nano-silica supported tetramethylguanidine and nano-silica supported quaternary ammonium base, and the loading amount is 8-15wt%.
[0014] In a preferred embodiment of the present invention, in step S2, the amount of the supported solid base catalyst added is 15-25% of the mass of the isocyanuric acid.
[0015] In a preferred embodiment of the present invention, in step S2, the distillation apparatus is a packed column or a plate column with a theoretical number of 5-15 plates, a cooling medium temperature of 5-15°C in the top condenser, and a reflux ratio of 1:2-5.
[0016] In a preferred embodiment of the present invention, in step S3, the distance between the evaporation surface and the condensation surface of the first-stage short-path molecular distillation is 3-5 cm, and the feed rate is 2-5 kg / m³. 2 ·h.
[0017] In a preferred embodiment of the present invention, in step S3, the distance between the evaporation surface and the condensation surface of the second-stage short-path molecular distillation is 2-3 cm, and the feed rate is 1-3 kg / m³. 2 ·h.
[0018] In a preferred embodiment of the present invention, the dynamic viscosity of the low-viscosity TAIC at 25°C is 10.4-14.6 mPa·s.
[0019] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0020] (1) This invention uses isocyanuric acid and allyl methyl carbonate as raw materials, and selects a supported solid base for catalytic synthesis. During the reaction, vacuum distillation and inert gas purging are used to continuously remove byproducts in situ. Compared with existing processes, this invention can avoid the introduction of ionic impurities such as chloride ions, sulfide ions, and metal salts. The resulting product has a low base value and color, which can not only eliminate the inhibitory effect of impurities on the free radical polymerization of the photocuring system, but also ensure that the product has good storage stability.
[0021] (2) The present invention uses a supported solid base catalyst, which can be completely separated by filtration after the catalytic reaction is completed and can be recycled and reused, thus solving the problems of easy residue and product contamination of homogeneous catalysts. The by-products of the reaction system can be separated separately and utilized as resources, which not only improves the reaction efficiency and reaction selectivity, but also avoids the defects of traditional homogeneous catalytic processes that generate a large amount of saline organic wastewater and have great difficulty in post-treatment.
[0022] (3) This invention employs two-stage short-path molecular distillation for purification, which can effectively remove difficult-to-separate trace impurities such as oligomers, incompletely reacted intermediates, and chromogenic precursors. Commonly, products suffer from high viscosity, dark color, and insufficient thermal stability. This invention, through gradient purification, produces products with high purity, low viscosity, and minimal color change during thermal aging. When low-viscosity TAIC products are applied to solvent-free photocuring systems, good miscibility and leveling can be achieved without the addition of diluents or heating. Simultaneously, the cured products exhibit excellent resistance to UV yellowing, meeting the stringent requirements of photocurable materials for functional monomers. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a flowchart of the preparation process of the present invention. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0027] Unless otherwise specified in the following examples, all raw materials were commercially available or prepared using conventional methods in the art. Specifically, isocyanuric acid was purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity ≥98%; allyl methyl carbonate was purchased from Wuhan Kanos Technology Co., Ltd., with a purity ≥98%; N,N-dimethylformamide was purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity ≥99.5%; dimethyl sulfoxide was purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity ≥99.7%; and N-methylpyrrolidone was purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity ≥99.5%.
[0028] like Figure 1 As shown, a preparation process for low-viscosity TAIC for photocurable materials includes the following steps:
[0029] S1. Isocyanuric acid, allyl methyl carbonate, and a polar aprotic solvent are placed in a reaction vessel, stirred, and nitrogen is introduced to replace the air. A supported solid base catalyst is added. The reaction is stirred at 100-120℃ and 1.0×10⁴-3×10⁴ Pa for 6-8 hours. During the reaction, methanol is removed by distillation and carbon dioxide is removed by purging with inert gas to obtain the reaction solution.
[0030] S2. Cool the reaction solution to 30-45℃, filter to remove the supported solid base catalyst, and collect the filtrate; distill the filtrate under reduced pressure at 80-120℃ and 100-1000Pa using a thin-film evaporator to obtain crude TAIC.
[0031] S3. The crude TAIC is fed into the first-stage short-path molecular distillation apparatus and crudely separated and the middle distillate is collected under conditions of 120-140℃ and 0.05-0.10Pa. The middle distillate is then fed into the second-stage short-path molecular distillation apparatus and purified and the middle distillate is collected under conditions of 100-120℃ and 0.01-0.05Pa to obtain low-viscosity TAIC.
[0032] Specifically, step S1 is a nitrogen-site nucleophilic substitution reaction under alkaline conditions. The reactor is equipped with a mechanical stirring system, a temperature control system, a nitrogen protection system, a distillation device, and a vacuum system, which can achieve precise control of temperature and pressure and efficient removal of by-products during the reaction process.
[0033] Specifically, in step S1, isocyanuric acid, allyl methyl carbonate, and a polar aprotic solvent are added to the reaction vessel. The molar ratio of isocyanuric acid to allyl methyl carbonate is 1:3.0-5.0, and the mass ratio of the polar aprotic solvent to isocyanuric acid is 4-8:1. A polar aprotic solvent, selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, or N-methylpyrrolidone, is used as the reaction medium to stabilize the triketone skeleton structure of isocyanuric acid, suppress the ketone-enol isomerization side reaction, and effectively dissolve isocyanuric acid and allyl methyl carbonate, constructing a homogeneous reaction liquid environment, weakening intermolecular forces, and providing a suitable reaction microenvironment for nitrogen-hydrogen bond activation and nitrogen-site nucleophilic substitution reactions.
[0034] Next, the stirring system is started, and nitrogen gas is introduced into the reactor to replace the air inside. The stirring speed is set to 220-450 r / min, the nitrogen purity is ≥99.9%, and the replacement time is 15-30 min. This effectively isolates oxygen and trace amounts of water vapor, preventing the oxidation and deterioration of the allyl double bond, while also avoiding the consumption of alkaline catalytic sites on the supported solid base catalyst by moisture, thus ensuring the efficiency of subsequent catalytic reactions.
[0035] Furthermore, after nitrogen purging, the supported solid base catalyst is added to the reactor, and the temperature is increased to 100-120℃ at a rate of 3-5℃ / min to avoid local overheating of the material due to rapid heating, which could trigger side reactions such as allylic double bond polymerization. After reaching the set temperature, the vacuum pump is turned on, and the pressure inside the reactor is adjusted and maintained at 1.0 × 10⁻⁶. 4 -3×10 4 Pa, under reduced pressure and constant temperature stirring for 6-8 hours, yielded a reaction solution containing TAIC.
[0036] The supported solid base catalyst is selected from at least one of nano-silica supported tetramethylguanidine and nano-silica supported quaternary ammonium base, and the loading of the active component is 8-15 wt%; the amount of the supported solid base catalyst added is 10-25% of the mass of isocyanuric acid.
[0037] Specifically, those with a specific surface area of 280-350 m² 2 / g of dried nano-silica support was dried at 110℃ for 4h, cooled, and then sieved. Tetramethylguanidine was dissolved in anhydrous ethanol and mixed to form a uniform impregnation solution. The support was dispersed in the impregnation solution and impregnated by continuous stirring at 25℃ for 24h. After impregnation, the solvent was removed by vacuum distillation, the solid product was dried thoroughly at 100℃, and then activated at a constant temperature of 150℃. After cooling and sieving, the nano-silica supported tetramethylguanidine catalyst was obtained.
[0038] Specifically, the quaternary ammonium base is dissolved in anhydrous ethanol solvent and mixed and stirred to form a uniform impregnation solution; the dried nano-silica support is dispersed in the impregnation solution and impregnated by continuous stirring at 25°C for 24 hours; after impregnation, the solvent is removed by vacuum distillation, the solid product is fully dried at 100°C, and then activated at a constant temperature of 150°C. After cooling and sieving, the nano-silica supported quaternary ammonium base catalyst is obtained.
[0039] Specifically, under alkaline conditions in step S1, a supported solid base catalyst activates the nitrogen-hydrogen bond of isocyanuric acid, deprotonates it to generate a nitrogen anion, and undergoes a nucleophilic substitution reaction with the carbonyl carbon site of allyl methyl carbonate to complete the nitrogen-position allyl substitution. At the same time, the carbonate structure is simultaneously cracked to generate methanol and carbon dioxide as small molecule byproducts. Through multi-stage continuous nitrogen-position allyl substitution and intramolecular steady-state rearrangement, triallyl isocyanurate is generated.
[0040] Furthermore, a distillation unit is connected to the top of the reactor. This unit is either a packed column or a plate column, with a theoretical number of 5-15 plates. A condenser is installed at the top of the column, with a cooling medium temperature of 5-15°C and a reflux ratio controlled at 1:2-5. Methanol vaporizes under reduced pressure and enters the distillation unit. After condensation, it is collected in a receiving tank, achieving continuous removal and recovery of methanol. A nitrogen inlet pipe is installed at the bottom of the reactor. Nitrogen gas is evenly injected into the reaction liquid via a gas distributor at a flow rate of 0.5-3.0 L / min. Carbon dioxide is carried out of the reaction system by the nitrogen gas flow and enters an alkaline absorption device for fixation and collection. Continuous removal of methanol and carbon dioxide under reduced pressure promotes the forward reaction of the substitution reaction, improves the conversion rate of raw materials and the selectivity of the trisubstituted target product, and reduces the residue of monosubstituted and disubstituted intermediates, thereby obtaining high-purity TAIC.
[0041] Furthermore, step S2 involves catalyst separation and solvent recovery, which enables catalyst recycling and solvent recovery, reducing production costs and emissions of waste.
[0042] Specifically, after the reaction in step S1 is completed, the heating, vacuum, and stirring systems are turned off, and the reaction solution is cooled to 30-45℃. The reaction solution is then transferred to a precision solid-liquid separation device, using a microporous membrane pressure filtration device with a membrane pore size of 0.22-0.45μm to filter out the supported solid base catalyst. During filtration, the catalyst is washed 2-3 times with the same polar aprotic solvent as the reaction system, and the washing liquid is combined with the filtrate. The collected solid catalyst can be recycled after being washed with an organic solvent and dried at low temperature.
[0043] Further, the combined filtrate is fed into a scraped-film evaporator for vacuum distillation. The scraped-film evaporator includes a cylindrical heating jacket, a rotating scraper, a material distributor, a gas-liquid separation chamber, and a vacuum interface. The evaporator operating temperature is set at 80-120℃, the operating pressure at 100-1000Pa, and the scraper rotation speed at 100-500 r / min. The filtrate is evenly coated onto the evaporation wall by the material distributor, forming a uniform liquid film with a thickness of 0.1-1.0 mm. The residence time of the filtrate on the evaporation wall is 10-60 s, effectively avoiding side reactions caused by prolonged heating of the material.
[0044] Specifically, the filtrate is rapidly heated under a thin liquid film state on the cylinder wall, and the low-boiling-point polar aprotic solvent and the unreacted excess allyl methyl carbonate are rapidly vaporized. The light gas phase components enter the condensation system for liquefaction and recovery, and are recycled. The non-volatile triallyl isocyanurate, high-boiling intermediates and trace oligomers remain in the heavy liquid phase components and are continuously discharged from the bottom of the equipment to obtain crude TAIC.
[0045] Furthermore, step S3 is a two-stage short-path molecular distillation purification, which relies on the difference in the mean free path of different molecules under high vacuum and low temperature separation environment to achieve the segmented removal of light impurities, intermediates, and high-boiling oligomers.
[0046] Specifically, the crude TAIC is fed into the first-stage short-path molecular distillation unit, with the feed rate controlled at 2-5 kg / m³. 2 •h, with a distance of 3-5cm between the evaporation surface and the condensation surface, coarse separation is carried out at 120-140℃ and 0.05-0.10Pa.
[0047] Specifically, the feed material is evenly spread on the heating surface. The residual allyl methyl carbonate and trace amounts of methanol, etc., have a longer mean free path and preferentially contact the built-in condensing surface to condense and precipitate. They are distilled from the top and enter the light component collection tank, where the middle distillate is collected. The oligomers and tar-like high-boiling impurities have a shorter mean free path and are difficult to reach the condensing surface. They are discharged from the bottom as heavy components and enter the heavy component collection tank.
[0048] Furthermore, the middle distillate from the first-stage short-path molecular distillation unit is fed into the second-stage short-path molecular distillation unit, with the feed rate controlled at 1-3 kg / m³. 2 The evaporation and condensation surfaces are spaced 2-3 cm apart, and the fractionation is carried out at 100-120℃ and 0.01-0.05 Pa. Trace light impurities in the system are distilled off from the top of the equipment; residual oligomers and other heavy components are discharged from the bottom of the equipment; the middle distillate is collected to obtain low-viscosity TAIC.
[0049] Example 1:
[0050] Step S1: Isocyanuric acid, allyl methyl carbonate, and N-methylpyrrolidone are added sequentially to the reactor. The molar ratio of isocyanuric acid to allyl methyl carbonate is 1:3.0, and the mass ratio of N-methylpyrrolidone to isocyanuric acid is 6:1. Stirring is started at 350 r / min, and nitrogen is continuously introduced to purge the air from the reactor for 20 min. After purging, a nano-silica-supported tetramethylguanidine catalyst is added, with an active component loading of 12 wt% and a catalyst addition amount equal to 18% of the isocyanuric acid mass. The temperature is increased to 110°C at a rate of 4°C / min, and the pressure inside the reactor is maintained stably at 2 × 10⁻⁶. 4 The reaction was carried out under constant temperature and stirring for 6 hours. During the reaction, the top of the reactor was connected to a distillation unit, which was a packed column with 8 theoretical plates. The cooling medium temperature of the condenser at the top of the column was 10°C, and the reflux ratio was controlled at 1:3. The methanol generated in the reaction was continuously removed by distillation and condensation. Nitrogen gas was continuously bubbled at the bottom of the reactor, which carried out the carbon dioxide generated in the reaction. The carbon dioxide was collected by passing it into an alkaline absorption device. After the reaction was completed, the reaction solution was obtained.
[0051] Step S3: Cool the reaction solution to 35℃, and use a 0.30μm microporous membrane to filter and separate the nano-silica-supported tetramethylguanidine catalyst under pressure. Wash the catalyst twice with N-methylpyrrolidone, and combine the washing liquids into the filtrate. Transfer the filtrate to a scraped thin-film evaporator, control the evaporation temperature at 100℃, the operating pressure at 500Pa, and the scraper speed at 300r / min. The material forms a uniform liquid film on the evaporation wall and the residence time is controlled at 45s to obtain crude TAIC.
[0052] Step S3: Feed the crude TAIC into the first-stage short-path molecular distillation unit, controlling the feed rate to a fixed 3 kg / m³. 2 The coarse fractionation was performed at 130℃ and 0.08 Pa with a distance of 4 cm between the evaporating and condensing surfaces, collecting the middle distillate. This middle distillate was then fed into a second-stage short-path molecular distillation unit with a fixed feed rate of 3 kg / m³. 2The evaporation surface and condensation surface were spaced 3 cm apart. The fractionation was carried out at 110 °C and 0.03 Pa. The middle distillate was collected to obtain low-viscosity TAIC.
[0053] Example 2:
[0054] Compared with Example 1, in this embodiment, the molar ratio of isocyanuric acid to allyl methyl carbonate in step S1 is 1:3.5, while the other material ratios, equipment conditions and process parameters remain unchanged.
[0055] Example 3:
[0056] Compared with Example 1, in this embodiment, the molar ratio of isocyanuric acid to allyl methyl carbonate in step S1 is 1:4.0, while the other material ratios, equipment conditions and process parameters remain unchanged.
[0057] Example 4:
[0058] Compared with Example 1, in this embodiment, the molar ratio of isocyanuric acid to allyl methyl carbonate in step S1 is 1:4.5, while the other material ratios, equipment conditions and process parameters remain unchanged.
[0059] Example 5:
[0060] Compared with Example 1, in this embodiment, the molar ratio of isocyanuric acid to allyl methyl carbonate in step S1 is 1:5.0, while the other material ratios, equipment conditions and process parameters remain unchanged.
[0061] Example 6:
[0062] Compared with Example 3, in step S1 of this embodiment, the amount of nano-silica-supported tetramethylguanidine catalyst added is 15% of the mass of isocyanuric acid, while the proportions of other materials, equipment conditions and process parameters remain unchanged.
[0063] Example 7:
[0064] Compared with Example 3, in step S1 of this embodiment, the amount of nano-silica-supported tetramethylguanidine catalyst added is 22% of the mass of isocyanuric acid, while the proportions of other materials, equipment conditions and process parameters remain unchanged.
[0065] Example 8:
[0066] Compared with Example 3, in step S1 of this embodiment, the amount of nano-silica-supported tetramethylguanidine catalyst added is 25% of the mass of isocyanuric acid, while the proportions of other materials, equipment conditions and process parameters remain unchanged.
[0067] Comparative Example 1:
[0068] Compared with Example 3, in step S1, an equal amount of unsupported tetramethylguanidine was used as a homogeneous catalyst to replace the nano-silica supported tetramethylguanidine solid base catalyst. The other material ratios, equipment conditions and process parameters remained unchanged.
[0069] Comparative Example 2:
[0070] Compared with Example 3, in this comparative example, the reaction pressure in step S1 is adjusted to atmospheric pressure, and the operation of continuous methanol removal by negative pressure distillation is not used. Only nitrogen bubbling is retained to carry out carbon dioxide. The other material ratios, equipment conditions and process parameters remain unchanged.
[0071] Comparative Example 3:
[0072] Compared with Example 3, this comparative example does not use two-stage short-path molecular distillation. The crude TAIC is purified by conventional vacuum distillation, while the other material ratios, equipment conditions and process parameters remain unchanged.
[0073] Experimental Example 1:
[0074] The following performance tests were performed on the samples obtained in Examples 1-8 and Comparative Examples 1-3.
[0075] The purity of TAIC samples was determined by gas chromatography (GC). The sample was dissolved in an organic solvent and injected into the gas chromatograph. The chromatogram was recorded, and the peak area of each component was calculated using the area normalization method. The sample purity was expressed as the percentage of the TAIC main peak area to the total peak area.
[0076] For the viscosity test at 25℃, an NDJ-1 rotational viscometer was used. The sample was placed in a constant temperature water bath, and the test environment temperature was controlled at (25±0.1)℃. After the sample was kept at a constant temperature for 30 minutes, the viscometer was started. After the reading stabilized, the data was recorded. The test was performed in parallel for 3 times, and the average value was taken as the dynamic viscosity of the sample at 25℃.
[0077] According to GB / T6324.6-2014 "Test Methods for Organic Chemical Products Part 6: Determination of Color of Liquids - Tristimulus Value Colorimetric Method", the sample was injected into a clean, dry 20mm optical path standard cuvette and placed in a tristimulus value colorimeter. The instrument zero point was calibrated with distilled water, and the instrument was calibrated using a platinum-cobalt standard color solution. The TAIC sample was measured under the same test conditions, and the platinum-cobalt color number displayed by the instrument was read. Three parallel measurements were performed, and the average value was taken as the initial platinum-cobalt color number measurement result. The TAIC sample was placed in a heat-resistant sealed container, and the container was heated in a constant temperature environment of 150℃ for 2 hours. After heating, it was removed, cooled to room temperature, and the platinum-cobalt color number after heat aging was measured.
[0078] For alkalinity determination, an automatic potentiometric titrator was used. A 0.01 mol / L hydrochloric acid standard solution was used as the titrant. The sample was dissolved in anhydrous ethanol, shaken well, and placed in the titration cell. A composite electrode was inserted, the titrator was turned on, and the hydrochloric acid standard solution was slowly added until a potential jump occurred. The volume of hydrochloric acid standard solution consumed at the titration endpoint was recorded, and the alkalinity of the sample (mgKOH / g) was calculated. The test was performed in triplicate, and the average value was taken for quantitative detection of the residual amount of free alkaline substances in the system.
[0079] By mass, 100 parts of low-viscosity TAIC monomer, 3 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 25 parts of bisphenol A epoxy acrylate were sequentially added to the mixing vessel of a high-speed stirrer. The stirring environment temperature was set to 25±0.1℃, the stirring speed was adjusted to 500 r / min, and stirring was continued for 10 min to obtain a photocurable mixture. The mixture was quantitatively transferred into a pre-cleaned, dry, and impurity-free mold using a precision pipette. The mold had a diameter of 50 mm and a thickness of 0.3 mm. Air bubbles were avoided during the transfer process. After the transfer was completed, the surface of the mixture was gently smoothed with a scraper to ensure that the mixture was evenly spread in the mold. The mold was then placed in a dust-free environment and allowed to stand for 5 min to remove any tiny air bubbles, resulting in a uniform thickness, homogeneous, and defect-free sample to be cured.
[0080] For the tests of photocuring inhibition time and surface drying time, the sample to be cured was placed under a UV curing machine. The UV lamp power was set to 80W, the irradiation distance to 10cm, and the ambient temperature to 25℃. A stopwatch was used to record the time from when the UV lamp was turned on until the system lost its fluidity and stopped stringing, which was taken as the inhibition time. The time from when the UV lamp was turned on until the sample surface was free of adhesion and marks when touched by a finger was taken as the surface drying time. The test was performed in parallel for 3 times and the average value was taken.
[0081] For the UV-accelerated yellowing resistance test, a QUV UV aging test chamber was used, with the UV lamp wavelength set to 340nm and the irradiation intensity to 0.8W / m². 2 The condensation cycle mode was adopted, the temperature was controlled at (40±2)℃, and the relative humidity was 60%±5%. The cured sample was placed on a quartz slide and continuously irradiated for 1000h. The yellowness value (YI) of the cured sample was measured by a colorimeter at 0h and 1000h of irradiation, and the yellowness change rate was calculated.
[0082] The test results are shown in Tables 1 and 2.
[0083]
[0084]
[0085] As shown in Table 1, the purity of the sample samples in the examples remained stable at 98.57-99.16%, and the viscosity remained stable at 10.4-14.6 mPa·s. The product of Example 3 achieved a purity of 99.16%, a viscosity of only 10.4 mPa·s at 25°C, an initial platinum-cobalt color of 11, and a gradual increase in color after 2 hours of heat aging at 150°C. Simultaneously, the alkalinity was as low as 0.022 mg KOH / g, indicating that the substitution reaction of this invention has high selectivity, low production of mono- and di-substituted intermediates and macromolecular oligomers, and that complete solid-liquid separation can be achieved using a supported solid alkaline catalyst, resulting in low residual free alkalinity in the system. Combined with high-vacuum molecular distillation purification, easily oxidized and discolored polar impurities and viscous components are effectively removed.
[0086] As shown in Table 2, the polymerization inhibition time of the examples ranged from 6.2 to 7.4 s, and the surface drying time ranged from 15.6 to 19.0 s. Overall, the curing induction cycle was short and the surface drying efficiency was stable. The slight differences between the different examples stemmed from the differences in the content of trace polar byproducts and unsaturated impurities. Groups with relatively higher impurity content consumed a small amount of photoinitiated active free radicals, resulting in a slight increase in polymerization inhibition and surface drying time. In terms of long-term weather resistance, after 1000 hours of accelerated UV aging, the yellowing rate of the photocurable films in the examples ranged from 2.43% to 4.09%. Samples with low impurity content and good component uniformity exhibited a dense and stable network structure after cross-linking, which could effectively resist UV oxidative degradation and significantly suppress the increase in yellowing. Overall, they met the long-term use requirements of solvent-free photocurable coatings and optical functional materials.
[0087] Comparative Example 1 used unsupported tetramethylguanidine as a homogeneous catalyst, which could not remove the alkaline components through post-treatment. The alkalinity was as high as 0.864 mg KOH / g, and the large amount of free alkali continuously inhibited the free radical polymerization reaction, with an inhibition time of 15.4 s and a surface drying time of 41.8 s. The curing process was severely hindered, and non-selective side reactions occurred frequently. The product purity was only 95.27%, and oligomers and colored impurities were enriched in large quantities. The initial color and heat-aged color increased significantly, and the UV yellowness change rate of the cured film reached 12.62%. Comparative Example 2 had insufficient substitution reaction, with a large amount of by-products remaining. The purity dropped to 94.61%, and the system viscosity was as high as 31.5 mPa·s, which seriously affected the leveling properties of the photocuring system. Complex impurity components were prone to aging and degradation under UV irradiation, and the yellowness change rate was 10.47%. Comparative Example 3 did not employ a two-stage molecular distillation deep refining process, resulting in the inability to effectively remove small molecule residues and viscous components. Its purity, viscosity, and color indicators were all inferior to those of the other examples. Long-term aging and accumulation of impurities led to a decrease in the weather resistance of the photocured product, with a yellowing rate of 7.73%. Overall, its application performance had significant shortcomings.
[0088] This invention uses isocyanuric acid and allyl methyl carbonate as reaction raw materials and supported solid alkali as catalyst. It combines solid-phase catalytic separation and two-stage short-range molecular distillation gradient purification to reduce the content of alkaline residue, unsaturated intermediates and macromolecular oligomers in the product. While ensuring high purity, low viscosity and excellent thermal stability of the monomer, it eliminates the hidden danger of photocuring polymerization inhibition and improves the UV aging resistance and yellowing resistance of photocurable materials.
[0089] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A preparation process for low-viscosity TAIC for photocurable materials, characterized in that, Includes the following steps: S1. Isocyanuric acid, allyl methyl carbonate, and a polar aprotic solvent are placed in a reaction vessel, stirred, and nitrogen is introduced to replace the air. A supported solid base catalyst is added; the reaction is carried out at 100-120℃ and 1.0×10⁻⁶ ppm. 4 -3×10 4 The reaction was stirred at Pa for 6-8 hours. During the reaction, methanol was removed by distillation and carbon dioxide was removed by inert gas purging to obtain the reaction solution. S2. Cool the reaction solution to 30-45℃, filter to remove the supported solid base catalyst, and collect the filtrate; distill the filtrate under reduced pressure at 80-120℃ and 100-1000Pa using a thin-film evaporator to obtain crude TAIC. S3. The crude TAIC is fed into a first-stage short-path molecular distillation apparatus, and crudely separated and the middle distillate is collected under conditions of 120-140℃ and 0.05-0.10Pa. The middle distillate is then fed into a second-stage short-path molecular distillation apparatus, and refined and the middle distillate is collected under conditions of 100-120℃ and 0.01-0.05Pa to obtain the low-viscosity TAIC.
2. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S1, the molar ratio of isocyanuric acid to allyl methyl carbonate is 1:3.0-5.
0.
3. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S1, the polar aprotic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, or N-methylpyrrolidone.
4. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S1, the mass ratio of the polar aprotic solvent to the isocyanuric acid is 4-8:
1.
5. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S2, the supported solid base catalyst is selected from at least one of nano-silica supported tetramethylguanidine and nano-silica supported quaternary ammonium base, and the loading amount is 8-15 wt%.
6. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S2, the amount of the supported solid base catalyst added is 15-25% of the mass of the isocyanuric acid.
7. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S2, the distillation apparatus is a packed column or a plate column with a theoretical number of 5-15 plates, a cooling medium temperature of 5-15°C in the top condenser, and a reflux ratio of 1:2-5.
8. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S3, the distance between the evaporation surface and the condensation surface of the first-stage short-path molecular distillation is 3-5 cm, and the feed rate is 2-5 kg / m³. 2 ·h.
9. The preparation process of low-viscosity TAIC for photocurable materials according to claim 1, characterized in that: In step S3, the distance between the evaporation surface and the condensation surface of the second-stage short-path molecular distillation is 2-3 cm, and the feed rate is 1-3 kg / m³. 2 ·h.
10. A low-viscosity TAIC for photocurable materials, prepared according to the preparation process of any one of claims 1-9, characterized in that: The low-viscosity TAIC has a dynamic viscosity of 10.4-14.6 mPa·s at 25°C.